MOTIVATION OF NURSES TO WORK WITH HOSPITALIZED GERIATRIC PATIENTS - Diana Paskaleva; Stoilka Tufkova (Peytchinski Publishing, 2019)
Background: Motivation in the broadest sense is what affects the challenge, direction and maintenance of human behaviour. It has a leading role with healthcare professionals in carrying out their professional duties. Aim: The purpose of the study is to analyse the main reasons for choosing the nursing profession and what's the motivation to work with hospitalized geriatric patients among nursing practitioners. Materials and methods: Design: By its nature, the conducted observation is retrospective anamnestic. Data was obtained within the period from April 2014 to January 2016. The study includes an anonymous survey of 260 healthcare professionals (nurses) working in Surgical, Internal and Emergency Units with a predominant contingent of patients over the age of 65. Results: The analysis of the nurses' opinion about the reasons for practicing the nursing profession showed that the leading reason is the desire to care for and help the ones in need (83,1%). Conclusion: It is necessary to make immediate organizational changes and management decisions in order to create and implement an effective motivational strategy to assist medical professionals in carrying out their humane profession.